Inhalable liposomal delivery of osimertinib and DNA for treating primary and metastasis lung cancer - Xianglei Fu; Yanbin Shi; Hang Wu; Yankun Zhang; Yingying Liu; Xiaoyu Wan; Xiangqin Chen; Jiamin Zhou; Shengnan Qiu; Xiaogang Zhao; Zhongxian Tian; Lian Li; et al. (Nature Communications)
Abstract Lung cancer remains one of the most common malignancies, and its brain metastases significantly worsen the prognosis for patients. Current treatments for lung cancer face many challenges, including poor drug accumulation and the inability to simultaneously control primary and metastatic tumors. Here, we show that the mRNA-binding protein insulin-like growth factor 3 is crucial for non-small cell lung cancer progression and metastasis. We construct an inhalable nanoliposome system to co-deliver osimertinib and DNA plasmid for gene knockdown. Upon inhalation, these nanoparticles efficiently penetrate pulmonary barriers and accumulate in lungs by mimicking natural lung surfactants. Within tumor cells, released osimertinib inhibits tumor growth, while the DNA triggers the production of engineered exosomes that can travel to the brain to suppress tumors. This strategy effectively inhibits both primary and metastatic tumors while enhancing antitumor immune responses. This work suggests that this inhalable nanomedicine offers a safe and versatile strategy for cancer therapy.